1981
DOI: 10.1161/01.str.12.6.750
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of asymptomatic extracranial arterial disease.

Abstract: Investigations of the incidence and the extent of the asymptomatic early stages of extracranial arterial disease (EAD) have been restricted for methodical reasons. Direct Continuous Wave-Doppler examination has given highly accurate results in the location and correct estimation of the degree of EAD both for the carotid (97%) and the vertebral arteries (90%), as shown from a detailed comparison with carotid (n = 604) and vertebral (n = 426) angiograms. Compared with this degree of reliability, the validity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
68
0
7

Year Published

1983
1983
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(80 citation statements)
references
References 43 publications
5
68
0
7
Order By: Relevance
“…Earlier studies have shown a strong association between the prevalence of PAD and COD. 1,2,[6][7][8][9]11,12 Our study was consistent with these earlier prevalence studies because some disease was found at most of our patients' PAD and COD evaluations suggesting that there is a strong correlation between the prevalence of PAD and COD despite a weaker severity correlation. In summary, our study extended previous studies by looking at the correlation between the severity of PAD and COD.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Earlier studies have shown a strong association between the prevalence of PAD and COD. 1,2,[6][7][8][9]11,12 Our study was consistent with these earlier prevalence studies because some disease was found at most of our patients' PAD and COD evaluations suggesting that there is a strong correlation between the prevalence of PAD and COD despite a weaker severity correlation. In summary, our study extended previous studies by looking at the correlation between the severity of PAD and COD.…”
Section: Discussionsupporting
confidence: 90%
“…This is readily apparent from the fact that most of our patients had some disease at their evaluations for PAD and COD and supports the results of many earlier studies. 1,2,[6][7][8][9]11,12 Therefore, the correlation between disease severity may only be modest, but the correlation between prevalence of disease is significant.…”
Section: Discussionmentioning
confidence: 99%
“…A subclavian steal phenonemon can be reliably diagnosed by this non-invasive technique, but in contrast to the vertebral system a differentiation of the underlying vascular disease is not possible. The main problems are the investigation of the proximal part of the vertebral artery and the differentiation of severe stenosis, occlusion, hypoplasia and aplasia (von Reutern et al, 1976, Hennerici et al, 1981. Ultrasonic duplex scanning with spectral analysis of the Doppler signal is a very reliable technique for the detection of carotid atherosclerosis (Fell et al, 1981;Breslau, 1982;Ackerstaff et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Current knowledge on incidence and course of atherosclerosis mainly originates from patient based angiographic and Doppler followup evaluations which for methodological reasons are restricted to severe atherosclerosis. [20][21][22][23] Observation that specific ante mortem risk factors such as elevations in body-mass index, systolic blood pressure, serum LDL cholesterol, triglyceride concentration and cigarette smoking are significantly related to the extent of atherosclerotic lesions in young people. 24 In our study (Table 1) active and passive smoking are considered to be important risk factors for atherosclerotic disease in men.…”
Section: Discussionmentioning
confidence: 99%